2013
DOI: 10.1080/09297049.2013.824955
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal exposure to methyl mercury and neuropsychological development in 7-year-old urban inner-city children exposed to lead in the United States

Abstract: Background The most common route for general population exposure to methyl mercury (MeHg) is fish consumption. Recommendations to pregnant women about consuming fish contaminated with MeHg are also applied to children, but there are few studies available about the effects of low level postnatal MeHg exposure in them. Objectives To investigate the association between postnatal methyl mercury exposure and neuropsychological development in a study of children also exposed to lead, both measured at 7 years. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
1
4
1
Order By: Relevance
“…Mean hair Hg level in that study was 6.09 lg/g at 9 years and 8.0 lg/g at 17 years. The benefit of n3-PUFA content of the fish is hypothesized to outweigh the risk of MeHg exposure from fish intake [30]. Our findings of median hair Hg 1.40 (range: 0.31-3.96) lg/g are slightly lower than that of previous Japanese study, and mean hair Hg in our study (1.49 lg/g) is much lower than that of Seychelles cohort.…”
Section: Hgcontrasting
confidence: 56%
“…Mean hair Hg level in that study was 6.09 lg/g at 9 years and 8.0 lg/g at 17 years. The benefit of n3-PUFA content of the fish is hypothesized to outweigh the risk of MeHg exposure from fish intake [30]. Our findings of median hair Hg 1.40 (range: 0.31-3.96) lg/g are slightly lower than that of previous Japanese study, and mean hair Hg in our study (1.49 lg/g) is much lower than that of Seychelles cohort.…”
Section: Hgcontrasting
confidence: 56%
“…These dose-related effects have also been reported outside of Amazonia regions, such as the Faroe Islands where longitudinal work has found that every 10-ppm increase in Hg is associated with a 1.8 to 2.2-point mean decrease in IQ score [ 20 ]. The findings are consistent with other studies conducted across the globe [ 21 , 22 , 23 ] and provide strong evidence (with exceptions reported from studies in the Seychelle Islands [ 23 , 24 ] and the United States [ 25 ] that exposure to MeHg negatively impacts the general intelligence of humans.…”
Section: Introductionsupporting
confidence: 91%
“…In contrast, while it is true that evidence from associated studies has reported its neurotoxic impact, it is important to outline that there are also other longitudinal studies that differ not only among these, but also among themselves. Some studies have found that there are no patterns of alteration in the development of cognitive and/or neuropsychological skills (Boucher et al, 2010;Forns et al, 2014;, Lee et al, 2017;Wang et al, 2014). As for evidence of impairment, similar results to those cited above have also been found, which indicated impairment or diminution of neurocognitive functions in accordance with the final longitudinal analyses (Kim et al, 2018;Valeri et al, 2017;van Wijngaarden et al, 2017;Debes et al, 2016).…”
Section: Introductionmentioning
confidence: 57%